Analisis Strategi Penanganan Stunting di Desa Bangun Sari Kabupaten Kampar Provinsi Riau - Tia Harjianti; Dedi Afandi; Novita Rany; Doni Jepisah; Hastuti Marlina (LPPM Hang Tuah Pekanbaru, 2023)
Stunting is a condition of a child's growth disorder, namely the child's height is shorter (dwarf) than the standard age, which is <-2 SD. Kampar Regency is one of the highest-ranked stunting rates in Riau Province in 2018 which is 31.99% and increased in 2019 to 32.05%. The purpose of this study was to analyze the stunting management strategy in Bangun Sari Village, Kampar Regency, Riau Province. The study used qualitative methods through in-depth interviews, observation, and document review with 8 research informants. The results obtained are that there is still a lack of allocation of village funds budgeted by village officials. The health promotion provided has not been well received by the community. The inter-sectoral support that has been established has been running quite well. Food security has been provided and distributed, but in reality, the food aid is not consumed well by the community due to poor parenting by parents. Monitoring and evaluation have been carried out quite well. The conclusion of this study is that the commitment, vision, mission, health promotion, cross-sectoral support, food security, and monitoring of stunting have been sufficient and distributed by the UPTD of the Kampar Kiri Hilir Health Center.